Functional Analysis of Linking Adverbials in Chemistry and English Language Teaching - Seyed Foad Ebrahimi; Vafa Alboghobiesh (Colombian Applied Linguistics Journal)
Linking adverbials are important linguistic features that signal a cohesive link between parts of the discourse. This study intends to explore the frequencies and discourse functions of linking adverbials in research articles across two disciplines: English Language Teaching and Chemistry. To this end, a corpus of 40 research articles from each discipline were selected from high-prestige journals recommended by successful researchers in the respective fields. The selected research articles were taken from the 2018-2019 issues of the journals. Liu's (2008) updated and widely recognized classification of linking adverbials was employed to identify linking adverbials. Findings revealed the disciplinary differences concerning frequencies and functions of linking adverbials and categories and subcategories of linking adverbials. By comparing the results of this study with previous literature, it could be concluded that frequencies and functions of linking adverbials are imposed by the nature of discipline and genre.